Gender empowerment through ICTs: potential and challenges for women in the Caribbean - Muturi, Nancy W. (My University, 2010)
Information communication technologies (ICTs) have been promoted as tools for national development and for gender empowerment in many developing countries. In the Caribbean, governments, non-governmental organizations and training institutes play a key role in ensuring access to ICTs among women. Gender empowerment is equated to access to information and technology but there are several concerns related ICT access and their effective use among women that are not adequately addressed. This study addresses these issues as well as social, cultural, economic and other factors that challenge women’s access and use of communication technology. The study recommends further research in policy development to focus on identifies challenges and strategies that will ensure women’s participation in their own empowerment through ICTs.
Keywords: Information communication technologies; Women; Government; Non-governmental organizations; Gender empowerment